Human resources outsourcing and organizational culture: Differences and similarities between organizations that recur and not recur to HRO, in Portugal - Silva, M. G.; Pinheiro, M. L. (XXXIV Jornadas Luso-Espanholas de Gestão Científica (JLEGC 2025), 2025)
Human Resource Outsourcing (HRO) has become a strategic tool for organisations seeking to enhance operational efficiency, flexibility, and competitiveness. This study examines the context of HRO in Portugal, exploring the reasons for and against its use and investigating the role of organisational culture (OC) in shaping outsourcing decisions. Using a mixed-methods approach, data was gathered from 339 respondents across various industries. The findings reveal that HRO is primarily driven by legal compliance and access to specialised expertise, while concerns about losing control and the preference for internal knowledge development discourage its adoption. Although the study identified adaptability as a dominant organisational culture trait, no significant differences were found between organisations that use HRO and those that do not. This suggests that OC may not be as critical in outsourcing decisions as previously thought. The study provides a foundation for future research on the evolving role of HRO in organisational strategy.